Povos e comunidades tradicionais: relações com a escola do\no campo - Gonçalves, Marilei de Fátima Ferreira (2017)
The research seeks to lead to reflections on the Peoples and Traditional Communities (quilombolas, faxinalenses, peasants and beds). These communities have historically been excluded from national and educational discussions and public policies. Therefore, we defined as a general objective to problematize the reality of the quilombolas, faxinalenses, peasants, stonemasons and their relations with Formal Education, in the Municipal School of the Campo Augusto Pires de Paula (EMCAPP) and of the State College of Campo São Francisco de Assis (CECSFA), schools located in Campo Largo, in the Três Córregos District. For the development of the research, it was sought to build a theoretical framework which could support it, through theorists dedicated to research on the subject and also in the Policies and Programs focused on traditional communities, such as: National Policy on Sustainable Development Peoples and Traditional Communities (PNPCT), National Rural Education Policy and the National Program for Education in Agrarian Reform - PRONERA. The research instruments were interview script and semi-structured questionnaires for thirty-nine subjects. Including, students, teachers, residents of traditional communities. The results indicate that much still needs to be done in order to comply with the National Policy on the Education of the Field, the National Program for Education in Agrarian Reform - PRONERA, and the objectives of the National Policy for the Sustainable Development of Traditional Peoples and Communities. In particular, on de subject of an education with pedagogical practices that enable the empowerment of individuals, so that they can claim the recognition, strengthening and guarantee of territorial, social, environmental, economic and cultural rights. It is not enough the change of nomenclature of the Schools for Field Education, or Political Pedagogical Projects that include references of the Field Education. It must go further. It is necessary that teachers take ownership of the principles that guide the education of the countryside, of the traditional peoples and communities, which leads possibilities so that the students can have new options of works, without the need to abandon their customs and traditions. Thus, it is necessary to invest and encourage the continuous formation of teachers so that they can construct debates and questions in their pedagogical practices, involving the communities as participants in the management of the school and consequently of the management of the territory and the municipal education